Millable silicone rubber composition and cured silicone rubber

By using cyclosiloxanes with specific allyl groups content and surface-treated silicone in silicone rubber, combined with appropriate catalysts and process treatment, the problems of permanent compression deformation and yellowing in low-content, low molecular weight cyclosiloxane silicone rubber products are solved, achieving better performance and application range.

JP7660996B2Active Publication Date: 2025-04-14SHIN ETSU CHEMICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023523384
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-26
Filing Date
2022-05-02
Publication Date
2025-04-14
Estimated Expiration
2042-05-02

AI Technical Summary

Technical Problem

In the production of low content and low molecular weight cyclosiloxanes, it is difficult to effectively reduce the permanent compression deformation of the product, and when using organic peroxides as catalysts, the silicone rubber will become yellow, limiting its application range.

Method used

A low content of low molecular weight cyclosiloxane silicone containing a specific allyl group content and surface-treated silica gel are used as the main components, and an organic peroxide or an addition reaction catalyst is used as the catalyst. A low content of low molecular weight cyclosiloxane silicone rubber composition is prepared through process steps such as heat treatment and mixing.

Benefits of technology

The production of low-content, low molecular weight cyclosiloxane silicone rubber has been achieved, which reduces the permanent compression deformation of the product, and avoids the yellowing of the silicone rubber, expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660996000001
    Figure 0007660996000001
  • Figure 0007660996000002
    Figure 0007660996000002
  • Figure 0007660996000003
    Figure 0007660996000003
Patent Text Reader

Abstract

The present invention provides a millable-type silicone rubber composition that becomes a silicone rubber cured product that has a low content of low-molecular siloxane components, exhibits little change in the degree of plasticity of a silicone rubber compound, and has a low amount of compression set. This millable-type silicone rubber composition comprises: (A) an organopolysiloxane that is a condensate of (A-1) and (A-2); (B) processed silica that has been treated with a vinyl-group-containing alkoxysilane and / or a vinyl-group-containing organosiloxane and has a hydrophobicity of at least 40; and (C) a curing agent. (A-1) An organopolysiloxane that is represented by general formula (1) and is such that the content of low-molecular siloxane, having a degree of polymerization of less than or equal to 20, is less than 5,000 ppm (A-2) A silane represented by general formula (2) (in formula (1), R1 is a monovalent hydrocarbon group and m is a number from 2 to 1,000, and in formula (2), R2 is a monovalent hydrocarbon group and R3 is an alkyl group)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a millable silicone rubber composition and a cured silicone rubber product. [Background technology]

[0002] Silicone rubber generally has excellent weather resistance, durability, heat resistance, and colorability, and is also physiologically inactive, making it used in a wide range of fields, including building materials, electrical and electronic parts, office equipment, automotive parts, and medical devices.

[0003] As a method for producing linear organopolysiloxane, which is a raw material for silicone rubber, a method is known in which low molecular weight cyclic or linear organopolysiloxane is polymerized by equilibration reaction using an acidic or basic catalyst. However, in this polymerization method, the formation and cleavage of siloxane bonds occur simultaneously, so that the resulting high molecular weight linear organopolysiloxane contains a large amount of low molecular weight cyclic siloxane (hereinafter referred to as low molecular weight siloxane).

[0004] Under current chemical substance regulations, accumulation is generally evaluated using the BCF (Bioconcentration Factor). Although it is possible to more accurately evaluate accumulation in nature by collecting data in the actual environment, many chemical substances must be evaluated, and in terms of labor and cost, laboratory data called BCF is used as an index of accumulation.

[0005] BCF is a method to test the degree to which chemicals accumulate in fish in water, and experiments are conducted under constant concentrations of chemicals. Therefore, it is not a suitable method for evaluating the accumulation of poorly water-soluble or highly volatile substances. Although it has been shown that low molecular weight siloxanes of tetramers, pentamers, and hexamers (D4-6) have low accumulation and are almost harmless in the actual environment, they show high BCF values ​​and are therefore subject to regulation.

[0006] In Europe, D4-6 are designated as SVHC (Substances of Very High Concern). In Japan, D5, for which there was sufficient data, was not designated as a monitored chemical substance, but D4 and D6, for which data is insufficient, were designated as monitored chemical substances. In this global trend toward regulating chemical substances, there is a demand to reduce low molecular weight siloxanes.

[0007] As a method for producing an organopolysiloxane with a low content of low molecular weight siloxane, Patent Document 1 discloses a method in which a hydroxide selected from magnesium hydroxide, calcium hydroxide, strontium hydroxide, and barium hydroxide is added to an organopolysiloxane having at least one hydroxy group at the molecular chain terminal, and a polymer is obtained by a condensation polymerization reaction. However, with this method, the degree of polymerization of the product obtained is low, and it is difficult to obtain a raw rubber-like material.

[0008] Furthermore, Patent Document 2 discloses a method in which a silane or siloxane having a bifunctional dialkylaminosilyl group is added to an organopolysiloxane or triorganosilanol having silanol groups at both molecular chain terminals, and a polymer is obtained by a condensation polymerization reaction.

[0009] Patent Document 3 discloses a silicone rubber composition that is composed of a polyorganosiloxane-silethylene copolymer, reinforcing filler silica, and an organic peroxide, and that has a low content of volatile low-molecular-weight siloxanes.

[0010] Patent Document 4 discloses a silicone rubber composition in which finely powdered silica is mixed with an organopolysiloxane obtained by heating an organopolysiloxane having silanol groups at both molecular chain terminals and a silane or siloxane having two hydrolyzable groups in the molecule.

[0011] Patent Document 5 discloses a silicone rubber composition with a reduced content of low molecular weight siloxanes, which is obtained by heating a mixture of an organopolysiloxane having silanol groups at both molecular terminals, an end-capping agent such as triorganosilanol, a silane or siloxane having two dialkylaminosilyl groups in the molecule, and a reinforcing filler. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] Japanese Patent Application Publication No. 02-235931 [Patent Document 2] Japanese Patent Application Publication No. 07-026020 [Patent Document 3] Japanese Patent Application Publication No. 06-136270 [Patent Document 4] Japanese Patent Application Publication No. 06-322273 [Patent Document 5] Japanese Patent Application Publication No. 07-070441 Summary of the Invention [Problem to be solved by the invention]

[0013] The cured products of these conventional organopolysiloxanes with a low content of low molecular weight siloxanes may have large compression set. For example, when the cured products are used as packing, the packing remains crushed, and the effect as a packing is weakened. When used as a tube, the tube may not return to its original shape if it is used in a crushed or bent state, and when used as a roll, problems such as the tube remaining crushed may occur. In addition, although the silicone rubber composition of Patent Document 3 uses an organic peroxide as a curing agent, the silicone rubber cured product may yellow due to decomposition residue, and there are limitations to its use, such as it cannot be used in applications that come into contact with food, and post-cure is required to reduce these problems. There was a demand for the development of a millable type silicone rubber composition that would comply with chemical substance regulations, reduce the volatile components remaining in the product, be less likely to cause contact failure at electrical contacts, have no restrictions on use, and produce a cured silicone rubber product with excellent weather resistance, durability, heat resistance, etc., which are inherent to silicone rubber, and small permanent compression set. Therefore, an object of the present invention is to provide a millable type silicone rubber composition which has a low content of low molecular weight siloxane components, which causes little change in the plasticity of the silicone rubber compound, and which produces a cured silicone rubber with small compression set. [Means for solving the problem]

[0014] As a result of intensive research into solving the above problems, the inventors have discovered that the above object can be achieved by the following millable type silicone rubber composition which contains an organopolysiloxane component having a specific alkenyl group content and a specific surface-treated silica, and have thus completed the present invention. That is, the present invention provides the following millable type silicone rubber composition and its cured product, i.e., a silicone rubber cured product.

[0015] <1> (A) a condensation product of the following (A-1) and (A-2): 100 parts by mass of an organopolysiloxane in which alkenyl groups bonded to silicon atoms in components (A-1) and (A-2) account for 0.03 to 0.30 mol % of substituents other than alkenyl groups bonded to silicon atoms in components (A-1) and (A-2), (A-1) An organopolysiloxane having silanol groups at both molecular chain terminals and represented by the following general formula (1), which has a content of low-molecular-weight siloxanes with a degree of polymerization of 20 or less of less than 5,000 ppm: [ka] (In formula (1), R 1 may be the same or different and are monovalent hydrocarbon groups having 1 to 12 carbon atoms, and m is a number from 2 to 1,000. (A-2) A silane having two dialkylaminosilyl groups in one molecule, represented by the following general formula (2): [ka] (In formula (2), R 2 may be the same or different and are monovalent hydrocarbon groups having 1 to 12 carbon atoms; R 3 may be the same or different and are alkyl groups having 1 to 4 carbon atoms.) (B) 5 to 100 parts by mass of treated silica having a hydrophobicity of 40 or more and treated with a vinyl group-containing alkoxysilane and / or a vinyl group-containing organosilazane, and (C) Effective amount of hardener A millable type silicone rubber composition comprising: <2> The component (B) is a treated silica that has been treated with the vinyl group-containing alkoxysilane and / or vinyl group-containing organosilazane in an amount such that the vinyl group is 0.0001 mole or more per 100 parts by mass of silica. <1> 2. The millable type silicone rubber composition according to claim 1 . <3> The component (C) is an addition reaction curing agent which is a combination of an organohydrogenpolysiloxane and a hydrosilylation catalyst. <1> or <2> 2. The millable type silicone rubber composition according to claim 1 . <4> The component (C) is an organic peroxide curing agent. <1> or <2> 2. The millable type silicone rubber composition according to claim 1 . <5> <1> from <4> 2. A cured product of the millable type silicone rubber composition according to claim 1. <6> The total amount of low molecular weight siloxane components with a degree of polymerization of 20 or less contained in the cured product is less than 5,000 ppm. <5> The cured product according to claim 1. In the present invention, the mixture of the above components (A) and (B) before the curing agent is added is referred to as the (millable type) silicone rubber compound, and the compound to which the curing agent is added is referred to as the (millable type) silicone rubber composition. Effect of the Invention

[0016] According to the millable type silicone rubber composition of the present invention, the total content of low molecular weight siloxane components having a degree of polymerization of 20 or less is less than 5,000 ppm, and it is possible to obtain a cured silicone rubber product which has excellent weather resistance, durability, heat resistance, etc., inherent to silicone rubber, and further has small compression set and can maintain its shape even if it is deformed during use, making it suitable for a variety of applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention will be described in detail below, but the present invention is not limited thereto.

[0018] [Component (A)] In the present invention, component (A) is the main component (base polymer) in a millable type silicone rubber composition and is an organopolysiloxane which is a condensation product of (A-1) an organopolysiloxane having silanol groups at both molecular chain terminals and represented by the following general formula (1), which contains less than 5,000 ppm of low molecular weight siloxanes with a degree of polymerization of 20 or less, and (A-2) a silane having two dialkylaminosilyl groups in one molecule and represented by the following general formula (2): General formula (1): [ka] (In formula (1), R 1 may be the same or different and are monovalent hydrocarbon groups having 1 to 12 carbon atoms, and m is a number from 2 to 1,000. General formula (2): [ka] (In formula (2), R 2 may be the same or different and are monovalent hydrocarbon groups having 1 to 12 carbon atoms; R 3 may be the same or different and are alkyl groups having 1 to 4 carbon atoms.)

[0019] In the above general formula (1), R 1are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms. As the monovalent hydrocarbon group, those having 1 to 8 carbon atoms are particularly preferred, and specific examples thereof include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and octyl; cycloalkyl groups such as cyclopentyl and cyclohexyl; alkenyl groups such as vinyl, allyl, propenyl, butenyl, and hexenyl; cycloalkenyl groups such as cyclohexenyl; aryl groups such as phenyl and tolyl; and aralkyl groups such as benzyl and 2-phenylethyl. Of the above, methyl, vinyl, and phenyl groups are preferred, and methyl and vinyl groups are particularly preferred.

[0020] The degree of polymerization of the component (A-1) is from 2 to 1,000, and preferably from 10 to 800. If the degree of polymerization is greater than 1,000, it becomes difficult to remove low-molecular-weight siloxanes with a degree of polymerization of 20 or less.

[0021] In this specification, the degree of polymerization refers to the number-average degree of polymerization measured by gel permeation chromatography (GPC) under the conditions shown below, using polystyrene as a standard substance.

[0022] [Measurement conditions] Developing solvent: toluene Flow rate: 0.6mL / min Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-H TSKgel SuperH5000(6.0mmI.D.×15cm×1) TSKgel SuperH4000(6.0mmI.D.×15cm×1) TSKgel SuperH3000(6.0mmI.D.×15cm×1) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 50 μL (toluene solution with a concentration of 0.5% by mass)

[0023] The (A-1) component may be used alone or in the form of a mixture of two or more different molecular weights (degrees of polymerization) or molecular structures. The organopolysiloxane is also characterized in that the content of low molecular weight siloxanes with a degree of polymerization of 20 or less (when two or more types of low molecular weight siloxanes are contained, the total content of these) is less than 5,000 ppm. The content is preferably 3,000 ppm or less, more preferably 1,000 ppm or less (mass conversion). If the content of the low molecular weight siloxane is 5,000 ppm or more, it is not preferable because contact failure is likely to occur in the cured product containing the low molecular weight siloxane or environmental problems may occur. In the present invention, the content of low molecular weight siloxanes with a degree of polymerization of 20 or less was measured by gas chromatography under the following conditions using n-tetradecane as an internal standard.

[0024] [Measurement conditions] Equipment: Shimadzu Gas Chromatograph Nexis GC-2030 Carrier gas: Helium Flow rate: 0.6mL / min Detector: Flame ionization detector (FID) Detector temperature: 320℃ Column: DB-5MS (inner diameter 0.53 mmφ × length 30 m, packing material: silica) (Agilent Technologies) Column temperature: 50 → 280℃ (heating rate: 10℃ / min) Sample injection volume: 1.0 μL Internal standard: n-tetradecane

[0025] When the content of low molecular weight siloxanes having a degree of polymerization of 20 or less in the organopolysiloxane having silanol groups at both ends of the molecular chain represented by the general formula (1) is 5,000 ppm or more, the content of low molecular weight siloxanes is reduced to less than 5,000 ppm by a conventionally known method and used as the component (A-1) in the present invention. There are various known methods for removing low molecular weight siloxanes having a degree of polymerization of 20 or less from organopolysiloxanes, including a heating distillation method, a vacuum distillation method, and a thin film distillation method. In order to efficiently remove low molecular weight siloxanes, a high temperature under reduced pressure is preferable, but if the temperature is too high, the organopolysiloxanes will crack, so it is preferable to remove them at 100 to 300 ° C.

[0026] Component (A-2) contains two dialkylaminosilyl groups in each molecule, and condenses with the silanol groups in component (A-1) to form a high-viscosity polyorganosiloxane. In general formula (2), R 2 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms. As the monovalent hydrocarbon group, those having 1 to 8 carbon atoms are particularly preferred, and specific examples thereof include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and octyl; cycloalkyl groups such as cyclopentyl and cyclohexyl; alkenyl groups such as vinyl, allyl, propenyl, butenyl, and hexenyl; cycloalkenyl groups such as cyclohexenyl; aryl groups such as phenyl and tolyl; and aralkyl groups such as benzyl and 2-phenylethyl. R 2 As the alkyl group, a methyl group, an ethyl group and a vinyl group are preferred. In addition, in the general formula (2), R 3 are each independently an alkyl group having 1 to 4 carbon atoms. Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, a propyl group, and a butyl group, and among these, a methyl group and an ethyl group are preferable. Examples of the (A-2) component include bis(dimethylamino)dimethylsilane, bis(dimethylamino)diethylsilane, bis(diethylamino)methylvinylsilane, bis(diethylamino)dimethylsilane, bis(diethylamino)methylvinylsilane, etc. The (A-2) component may be used alone or as a mixture of two or more types having different molecular structures.

[0027] The condensation product of (A-1) and (A-2) of component (A) is obtained by mixing (A-1) and (A-2) and heating them. The mixing may be carried out so that (A-1) and (A-2) are mixed uniformly, and the heating may be carried out at a temperature of 30 to 230°C, preferably 70 to 200°C.

[0028] The amount of the (A-2) component added is preferably an amount such that the molar ratio of the dialkylaminosilyl group of the (A-2) component to the silanol group of the (A-1) component is 0.5 to 3.0. If the amount of the (A-2) component added is less than 0.5 moles per mole of the silanol group of the (A-1) component, the condensation polymerization is insufficient, and the molecular weight of the organopolysiloxane obtained by heating is small, and it may not become a millable silicone rubber. If the amount of the (A-2) component added is more than 3.0 moles per mole of the silanol group of the (A-1) component, it is necessary to remove the unreacted (A-2) component by heating, which is not economical.

[0029] The content of alkenyl groups bonded to silicon atoms in components (A-1) and (A-2) is 0.03 to 0.30 mol % relative to the substituents other than alkenyl groups bonded to silicon atoms in components (A-1) and (A-2). If the content of alkenyl groups is less than 0.03 mol %, addition vulcanization becomes difficult and the compression set becomes large, which is undesirable, while if it is more than 0.30 mol %, the compression set becomes large, which is undesirable. The alkenyl group is R 1 and R of the component (A-2) 2 It is sufficient that either one of them is present, and it may be present in both. The organopolysiloxane obtained by mixing the components (A-1) and (A-2) under heating may be a single type, or a mixture of two or more types differing in molecular weight (degree of polymerization) or molecular structure.

[0030] [(B) Component] Component (B) is treated silica having a hydrophobicity of 40 or more, preferably 50 to 70, and is treated with a vinyl group-containing alkoxysilane and / or a vinyl group-containing organosilazane (alkenyl group-containing organosilane). If the hydrophobicity of the treated silica is less than 40, the plastic reversion of the silicone rubber compound will be large and it will be difficult to compound the treated silica with the organopolysiloxane. In the present invention, the degree of hydrophobicity is an index showing the degree to which the silica surface has been subjected to hydrophobic surface treatment, and refers to a value measured by the methanol titration method described below.

[0031] <Method for measuring hydrophobicity (methanol titration method)> Put 50 mL of pure water into a 200 mL beaker, add 0.2 g of sample, and stir with a magnetic stirrer. Place the tip of a burette containing methanol into the liquid, dropwise add methanol while stirring, and let Y mL be the amount of methanol added until the sample is completely dispersed in the water. The amount is calculated using the following formula: Hydrophobicity = {Y / (50+Y)} x 100

[0032] The treated silica of component (B) is preferably treated with a vinyl-containing alkoxysilane and / or vinyl-containing organosilazane in an amount of 0.0001 mole or more of vinyl groups per 100 parts by mass of silica. If the amount of vinyl groups in the vinyl-containing alkoxysilane and / or vinyl-containing organosilazane added is 0.0001 mole or more, the compression set of the cured product will be favorable. The treated silica can be obtained, for example, by feeding fumed silica into a high-speed mixer, rotating it, and once the rotation has stabilized, spraying a hydrophobizing agent to obtain moist silica, which is then heated.

[0033] The amount of treated silica (B) blended is 5 to 100 parts by mass, and preferably 10 to 60 parts by mass, per 100 parts by mass of the organopolysiloxane (A). If the amount of component (B) blended is too small, the reinforcing effect is not obtained, whereas if the amount is too large, processability is deteriorated and the mechanical strength is reduced.

[0034] The alkenyl-containing organosilane for treating the silica is a vinyl-containing alkoxysilane and / or a vinyl-containing organosilazane. The vinyl group-containing alkoxysilane is not particularly limited, but examples thereof include vinyltriethoxysilane, vinyltrimethoxysilane, divinyldimethoxysilane, and vinyltris(methoxyethoxy)silane. The vinyl group-containing organosilazane is not particularly limited, but examples thereof include 1-vinylpentamethyldisilazane, 1,3-divinyl-1,1,3,3-tetramethyldisilazane, 1,3-dimethyl-1,1,3,3-tetravinyldisilazane, and 1,3-divinyl-1,1,3,3-tetravinyldisilazane, with 1,3-divinyl-1,1,3,3-tetramethyldisilazane being preferred. In the present invention, because the silica is treated in advance with such an alkenyl group-containing organosilane, not only is there no effect from the low molecular weight siloxane derived from the surface treatment agent, but the change in plasticity of the silicone rubber compound is small, and a cured silicone rubber with small compression set can be obtained.

[0035] [(C) component] The curing agent is not particularly limited as long as it can cure the silicone rubber compound, and examples thereof include the following (C-1) addition reaction curing agents and (C-2) organic peroxide curing agents.

[0036] (C-1) Addition reaction curing agent As the addition reaction curing agent (C-1), a combination of an organohydrogenpolysiloxane and a hydrosilylation catalyst is used. As the organohydrogenpolysiloxane, as long as it contains hydrogen atoms (i.e., hydrosilyl groups) bonded to two or more, preferably three or more, more preferably 3 to 200, still more preferably about 4 to 100 silicon atoms in one molecule, its molecular structure may be any of linear, cyclic, branched, and three-dimensional network structures. As the organohydrogenpolysiloxane, a known organohydrogenpolysiloxane as a crosslinking agent for an addition reaction curable silicone rubber composition can be used. For example, an organohydrogenpolysiloxane represented by the following average composition formula (3) can be used.

[0037] R 4 r H s SiO (4-r-s) / 2 (3) In the above average composition formula (3), R 4 represents an unsubstituted or substituted monovalent hydrocarbon group, which may be the same or different, and is preferably one excluding aliphatic unsaturated bonds. Usually, those having 1 to 12 carbon atoms, particularly 1 to 8 carbon atoms, are preferred. Specifically, alkyl groups such as methyl group, ethyl group, and propyl group; cycloalkyl groups such as cyclohexyl group; aryl groups such as phenyl group and tolyl group; aralkyl groups such as benzyl group, 2-phenylethyl group, and 2-phenylpropyl group; and groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms or the like, for example, 3,3,3-trifluoropropyl group, etc. can be mentioned. In the average composition formula (3), r satisfies 0 < r < 3, preferably 0.5 ≤ r ≤ 2.2, more preferably 1.0 ≤ r ≤ 2.0, s satisfies 0 < s ≤ 3, preferably 0.002 ≤ s ≤ 1.1, more preferably 0.005 ≤ s ≤ 1, and r + s satisfies 0 < r + s ≤ 3, preferably 1 ≤ r + s ≤ 3, more preferably 1.002 ≤ r + s ≤ 2.7.

[0038] The organohydrogenpolysiloxane has two or more hydrosilyl groups, preferably three or more, in one molecule, which may be at the molecular chain terminal, in the middle of the molecular chain, or both. The organohydrogenpolysiloxane preferably has a viscosity at 25°C of 0.5 to 10,000 mPa·s, particularly 1 to 300 mPa·s. The viscosity is a value measured by a rotational viscometer at 25°C (hereinafter the same).

[0039] Specific examples of such organohydrogenpolysiloxanes include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(hydrogendimethylsiloxy)methylsilane, tris(hydrogendimethylsiloxy)phenylsilane, methylhydrogencyclopolysiloxane, methylhydrogensiloxane-dimethylsiloxane cyclic copolymer, methylhydrogenpolysiloxane capped with trimethylsiloxy groups at both ends, dimethylsiloxane-methylhydrogensiloxane copolymer capped with trimethylsiloxy groups at both ends, dimethylpolysiloxane capped with dimethylhydrogensiloxy groups at both ends, dimethylsiloxane-methylhydrogensiloxane copolymer ... Methylsiloxane-methylhydrogensiloxane copolymer, methylhydrogensiloxane-diphenylsiloxane copolymer with trimethylsiloxy groups at both ends, methylhydrogensiloxane-diphenylsiloxane-dimethylsiloxane copolymer with trimethylsiloxy groups at both ends, methylhydrogensiloxane-methylphenylsiloxane-dimethylsiloxane copolymer with trimethylsiloxy groups at both ends, methylhydrogensiloxane-dimethylsiloxane-diphenylsiloxane copolymer with dimethylhydrogensiloxy groups at both ends, methylhydrogensiloxane-dimethylsiloxane-methylphenylsiloxane copolymer with dimethylhydrogensiloxy groups at both ends, (CH3)2HSiO 1 / 2 Units and (CH3)3SiO 1 / 2 Units and SiO 4 / 2 A copolymer consisting of (CH3)2HSiO units. 1 / 2 Units and SiO4 / 2 A copolymer consisting of (CH3)2HSiO units. 1 / 2 Units and SiO 4 / 2 Units and (C6H5)3SiO 1 / 2 and copolymers consisting of these units, and compounds in which part or all of the methyl groups in the above exemplary compounds have been substituted with other alkyl groups, phenyl groups, or the like.

[0040] The amount of the organohydrogenpolysiloxane is preferably 0.1 to 40 parts by mass per 100 parts by mass of component (A). The ratio of hydrogen atoms (hydrosilyl groups) bonded to silicon atoms per aliphatic unsaturated bond (such as an alkenyl group and a diene group) in components (A) and (B) is preferably in the range of 0.5 to 10, and more preferably 0.7 to 10. If the number of hydrogen atoms (hydrosilyl groups) bonded to silicon atoms per aliphatic unsaturated bond in components (A) and (B) is 0.5 or more, crosslinking is sufficient and sufficient mechanical strength is obtained, and if the number is 10 or less, the physical properties after curing are not reduced, and in particular, the heat resistance is not deteriorated and the compression set is not increased.

[0041] The hydrosilylation catalyst is a catalyst that causes a hydrosilylation addition reaction between the alkenyl group of component (A) (if present) or the alkenyl group (vinyl group) of component (B) and the silicon-bonded hydrogen atom (hydrosilyl group) of the organohydrogenpolysiloxane. Examples of the hydrosilylation catalyst include platinum group metal catalysts, including simple platinum group metals and their compounds, and those that have been known as catalysts for addition reaction curing silicone rubber compositions can be used. For example, platinum catalysts such as particulate platinum metal adsorbed on a carrier such as silica, alumina, or silica gel, platinic chloride, chloroplatinic acid, and alcohol solutions of chloroplatinic acid hexahydrate, palladium catalysts, and rhodium catalysts can be mentioned, with platinum or platinum compounds (platinum catalysts) being preferred.

[0042] The amount of catalyst added may be any amount sufficient to promote the addition reaction, and is usually used in the range of 1 ppm by mass to 1% by mass calculated as the amount of platinum group metal relative to the silicone rubber compound, with a range of 10 to 500 ppm by mass being preferred. If the amount added is 1 ppm by mass or more, the addition reaction is sufficiently promoted and curing is sufficient, while if it is 1% by mass or less, sufficient reactivity is obtained and it is not uneconomical. In addition to the above catalysts, an addition reaction inhibitor may be used according to the purpose of the present invention in order to adjust the curing rate. Specific examples of such an inhibitor include acetylene alcohol inhibitors such as ethynylcyclohexanol, tetracyclomethylvinylpolysiloxane, etc. The addition reaction inhibitor may be used alone or in combination of two or more types.

[0043] (C-2) Organic peroxide curing agent Examples of the (C-2) organic peroxide curing agent include benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, p-methylbenzoyl peroxide, o-methylbenzoyl peroxide, 2,4-dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, di-t-butyl peroxide, t-butyl perbenzoate, and 1,6-hexanediol-bis-t-butylperoxycarbonate.

[0044] The amount of organic peroxide curing agent added is preferably 0.1 to 10 parts by mass, particularly preferably 0.2 to 5 parts by mass, per 100 parts by mass of component (A). If the amount is 0.1 part by mass or more, curing will not be insufficient, and if it is 10 parts by mass or less, the silicone rubber cured product will not yellow due to the decomposition residue of the organic peroxide curing agent. Note that it is also possible to make a co-vulcanization type silicone rubber composition using an addition reaction curing agent and an organic peroxide curing agent in combination by combining and blending components (C-1) and (C-2) in the above-mentioned ranges of blending amounts with component (A).

[0045] The (C-1) component and the (C-2) component can be used according to the purpose. For example, when an addition reaction curing agent is used for electric wire applications, problems such as adhesion to the core wire may occur, so it is preferable to use an organic peroxide curing agent. In addition, for applications that come into contact with food, such as food trays, the use of an addition reaction curing agent is preferable because of concerns about the effects of decomposition residues of the organic peroxide curing agent.

[0046] [Other ingredients] In addition to the above-mentioned components, the silicone rubber composition of the present invention may optionally contain, as necessary, fillers such as crushed quartz, crystalline silica, diatomaceous earth, calcium carbonate, etc., colorants, tear strength improvers, acid acceptors, thermal conductivity improvers such as alumina, boron nitride, etc., release agents, reaction regulators, various alkoxysilanes as dispersants for fillers, particularly phenyl group-containing alkoxysilanes and their hydrolysates, diphenylsilanediol, carbon functional silane, and other fillers and additives known in thermosetting silicone rubber compositions.

[0047] <Curing conditions> The millable silicone rubber composition of the present invention can be cured by a known curing method under known curing conditions. Specifically, the composition can be cured by heating at 25 to 200° C., preferably 80 to 160° C. The heating time may be about 0.5 minutes to 5 hours, and particularly about 1 minute to 3 hours. The millable silicone rubber composition of the present invention described above uses a combination of the organopolysiloxane (A) and the treated silica (B), resulting in a millable silicone rubber composition with low low molecular weight siloxane content and small compression set of the cured product.

[0048] [Cured silicone rubber] The silicone rubber cured product of the present invention is a cured product of the millable type silicone rubber composition of the present invention. Therefore, the silicone rubber cured product of the present invention has a small amount of low molecular weight siloxane components and exhibits small compression set. For example, the silicone rubber cured product of the present invention may have a total content of low molecular weight siloxane components with a degree of polymerization of 20 or less of less than 5,000 ppm. EXAMPLES

[0049] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these.

[0050] [Preparation Examples 1 and 2, Comparative Preparation Examples 1 and 2] The hydrophobicity in the following Preparation Examples and Comparative Preparation Examples was measured by the following method. <Method for measuring hydrophobicity (methanol titration method)> Put 50mL of pure water into a 200mL beaker, add 0.2g of sample, and stir with a magnetic stirrer. Place the tip of a burette containing methanol into the liquid, dropwise add methanol while stirring, and the amount of methanol added until the sample is completely dispersed in water is YmL, which is calculated using the following formula. The hydrophobicity of the following treated silicas 1 to 4 is shown in Table 1. Hydrophobicity = {Y / (50+Y)} x 100

[0051] [Preparation Example 1] 200 g of fumed silica (Aerosil 200, Nippon Aerosil Co., Ltd.) was placed in a high-speed mixer (volume 10 L) and operated at 1,500 rpm. When the rotation became stable, 20 g of dimethylpolysiloxane having silanol groups at both ends, an average degree of polymerization of 4, and a viscosity of 15 mPa·s at 25°C as a hydrophobizing agent, and 1.2 g of vinyltrimethoxysilane were sprayed in 20 seconds to obtain wet silica. 100 g of this wet silica was placed in a 2 L flask and heated at 250°C for 2.5 hours. The resulting treated silica 1 had a hydrophobicity of 62 as measured by methanol titration.

[0052] [Preparation Example 2] Treated silica 2 was prepared in the same manner as in Preparation Example 1, except that the amount of vinyltrimethoxysilane was 0.6 g. Treated silica 2 thus obtained had a hydrophobicity of 61 as measured by methanol titration.

[0053] [Comparative Preparation Example 1] Except for not adding vinyltrimethoxysilane, treated silica 3 was prepared in the same manner as in Preparation Example 1. The obtained treated silica 3 had a hydrophobicity of 60 as measured by methanol titration.

[0054] [Comparative Preparation Example 2] Treated silica 4 was prepared in the same manner as in Preparation Example 1, except that 10 g of dimethylpolysiloxane having silanol groups at both ends, an average degree of polymerization of 4, and a viscosity of 15 mPa s at 25°C was used. The resulting treated silica 4 had a hydrophobicity of 35 as measured by methanol titration.

[0055] The contents of low molecular weight siloxane components with a degree of polymerization of 20 or less contained in the dimethylsiloxanes (A-1-1), (A-1-2), (A-1-3), (A-1-4), and (A-1-5) terminated with silanol at both ends and polymers 1 to 8 used in the synthesis examples below were determined under the following conditions. Note that, since no low molecular weight siloxanes with a degree of polymerization of 2 or less were detected, hereinafter the contents of low molecular weight siloxane components with a degree of polymerization of 20 or less determined under the following conditions may be expressed as ΣD3 to 20.

[0056] [Measurement conditions] Equipment: Shimadzu Gas Chromatograph Nexis GC-2030 Carrier gas: Helium Flow rate: 0.6mL / min Detector: Flame ionization detector (FID) Detector temperature: 320℃ Column: DB-5MS (inner diameter 0.53 mmφ × length 30 m, packing material: silica) (Agilent Technologies) Column temperature: 50 → 280℃ (heating rate: 10℃ / min) Sample injection volume: 1.0 μL Internal standard: n-tetradecane

[0057] [Synthesis Example 1] 100g of dimethylsiloxane with silanol at both ends (low molecular weight siloxane component content ΣD3-20: 700ppm) represented by the following formula (A-1-1) and 0.83g of bis(diethylamino)methylvinylsilane (A-2-1) were charged into a separable flask and stirred at room temperature for 1 hour, after which the temperature was raised to 180°C and condensation polymerization was carried out for 2 hours with stirring. The obtained polymer 1 had an average degree of polymerization of 7,000 and a low molecular weight siloxane component content ΣD3-20 of 520ppm. [ka]

[0058] [Synthesis Example 2] Except for using 0.41 g of bis(diethylamino)methylvinylsilane (A-2-1) and 0.39 g of bis(diethylamino)dimethylsilane (A-2-2) instead of 0.83 g of bis(diethylamino)methylvinylsilane (A-2-1), condensation polymerization was carried out in the same manner as in Synthesis Example 1. The obtained polymer 2 had an average degree of polymerization of 7,200 and a low molecular weight siloxane component content ΣD3-20 of 540 ppm.

[0059] [Synthesis Example 3] 100g of dimethylsiloxane with silanol at both ends (low molecular weight siloxane component content ΣD3-20: 930ppm) represented by the following formula (A-1-2) and 0.35g of bis(diethylamino)methylvinylsilane (A-2-1) were charged into a separable flask and stirred at room temperature for 1 hour, after which the temperature was raised to 180°C and condensation polymerization was carried out for 2 hours with stirring. The obtained polymer 3 had an average degree of polymerization of 7,800 and a low molecular weight siloxane component content ΣD3-20 of 680ppm. [ka]

[0060] [Synthesis Example 4] 100g of dimethylsiloxane with silanol at both ends (low molecular weight siloxane component content ΣD3-20: 780ppm) represented by the following formula (A-1-3) and 0.78g of bis(diethylamino)dimethylsilane (A-2-2) were charged into a separable flask and stirred at room temperature for 1 hour, after which the temperature was raised to 180°C and condensation polymerization was carried out for 2 hours with stirring. The obtained polymer 4 had an average degree of polymerization of 6,800 and a low molecular weight siloxane component content ΣD3-20 of 590ppm. [ka]

[0061] [Synthesis Example 5] 100g of dimethylsiloxane with silanol at both ends (low molecular weight siloxane component content ΣD3-20: 980ppm) represented by the following formula (A-1-4) and 0.33g of bis(diethylamino)dimethylsilane (A-2-2) were charged into a separable flask and stirred at room temperature for 1 hour, after which the temperature was raised to 180°C and condensation polymerization was carried out for 2 hours with stirring. The obtained polymer 5 had an average degree of polymerization of 7,700 and a low molecular weight siloxane component content ΣD3-20 of 710ppm. [ka]

[0062] [Synthesis Example 6] 100g of dimethylsiloxane with silanol at both ends (low molecular weight siloxane component content ΣD3-20: 700ppm) represented by formula (A-1-1) and 0.78g of bis(diethylamino)dimethylsilane (A-2-2) were charged into a separable flask and stirred at room temperature for 1 hour, then the temperature was raised to 180°C and condensation polymerization was carried out for 2 hours while stirring. The obtained polymer 6 had an average degree of polymerization of 7,400 and a low molecular weight siloxane component content ΣD3-20 of 530ppm.

[0063] [Synthesis Example 7] 100g of dimethylsiloxane with silanol at both ends (low molecular weight siloxane component content ΣD3-20: 930ppm) represented by formula (A-1-2), 0.03g of bis(diethylamino)methylvinylsilane (A-2-1) and 0.30g of bis(diethylamino)dimethylsilane (A-2-2) were charged into a separable flask and stirred at room temperature for 1 hour, then the temperature was raised to 180°C and condensation polymerization was carried out for 2 hours while stirring. The obtained polymer 7 had an average degree of polymerization of 8,000 and a low molecular weight siloxane component content ΣD3-20 of 700ppm.

[0064] [Synthesis Example 8] 100g of dimethylsiloxane with silanol at both ends (low molecular weight siloxane component content ΣD3-20: 500ppm) represented by the following formula (A-1-5), 5.00g of bis(diethylamino)methylvinylsilane (A-2-1) and 6.09g of bis(diethylamino)dimethylsilane (A-2-2) were charged into a separable flask and stirred at room temperature for 1 hour, then the temperature was raised to 180°C and condensation polymerization was carried out for 4 hours while stirring. The obtained polymer 8 had an average degree of polymerization of 6,200 and a low molecular weight siloxane component content ΣD3-20 of 410ppm. [ka]

[0065] [Examples 1 to 7, Comparative Examples 1 to 6] The base compounds (1) to (12), silicone rubber compositions (1) to (13), and test sheets (1) to (13) were prepared as follows. The physical properties of the silicone rubber compounds (base compounds) and the cured silicone rubber (test sheets) were measured as follows.

[0066] <Rubber property measurement> The resulting silicone rubber cured product was measured for various physical properties (hardness (Durometer A), tensile strength, and elongation at break) in accordance with JIS K 6249:2003.

[0067] <Measurement of compression set> The compression set was measured by a method in accordance with JIS K 6262:2013 using a test piece for measuring compression set prepared in accordance with JIS K 6262:2013.

[0068] [Example 1] 35 parts by mass of treated silica 1 prepared in Preparation Example 1 was added to 100 parts by mass of polymer 1 synthesized in Synthesis Example 1, and then mixed in a kneader to prepare base compound (1). To 100 parts by mass of the base compound (1), 0.9 parts by mass of a methylhydrogenpolysiloxane (degree of polymerization: 38, hydrosilyl group concentration: 0.00725 mol / g) having hydrosilyl groups on the side chains as a curing agent, 0.04 parts by mass of ethynylcyclohexanol as a reaction inhibitor, and 0.05 parts by mass of a platinum catalyst (Pt concentration: 1% by mass) were added using a twin roll and mixed uniformly to produce a raw rubber-like silicone rubber composition (1). The composition was then heated at 120°C and 70 kgf / cm 2 The composition was press cured for 10 minutes under the conditions of 120°C, 70 kgf / cm to prepare a test sheet (1) having a thickness of 2 mm, and the hardness, tensile strength, and elongation at break were measured by the above-mentioned methods. 2 The compression set of the cured product obtained by press curing for 15 minutes under the above conditions was measured. The measurement results are shown in Table 4.

[0069] [Example 2] A base compound (2) was prepared in the same manner as in Example 1, except that polymer 2 synthesized in Synthesis Example 2 was used instead of polymer 1, and a silicone rubber composition (2) was prepared in the same manner as in Example 1. Using the obtained composition, a test sheet (2) was produced in the same manner as in Example 1, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 4.

[0070] [Example 3] A base compound (3) was prepared in the same manner as in Example 1, except that polymer 3 synthesized in Synthesis Example 3 was used instead of polymer 1, and a silicone rubber composition (3) was prepared in the same manner as in Example 1. Using the obtained composition, a test sheet (3) was produced in the same manner as in Example 1, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 4.

[0071] [Example 4] A base compound (4) was prepared in the same manner as in Example 1, except that polymer 4 synthesized in Synthesis Example 4 was used instead of polymer 1, and a silicone rubber composition (4) was prepared in the same manner as in Example 1. Using the obtained composition, a test sheet (4) was produced in the same manner as in Example 1, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 4.

[0072] [Example 5] A base compound (5) was prepared in the same manner as in Example 1, except that polymer 5 synthesized in Synthesis Example 5 was used instead of polymer 1, and a silicone rubber composition (5) was prepared in the same manner as in Example 1. A test sheet (5) was prepared using the obtained composition in the same manner as in Example 1, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 4.

[0073] [Example 6] 0.6 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane as a curing agent was added to 100 parts by mass of the base compound (2) using a two-roll mill and mixed uniformly to produce a raw rubber-like silicone rubber composition (6). The composition was then heated at 165°C and 70 kgf / cm 2 The composition was press cured for 10 minutes under the conditions of 165°C, 70 kgf / cm to prepare a test sheet (6) having a thickness of 2 mm, and the hardness, tensile strength, and elongation at break were measured in the same manner as above. 2 The compression set of the cured product obtained by press curing for 15 minutes under the above conditions was measured in the same manner as above. The measurement results are shown in Table 4.

[0074] [Example 7] A base compound (6) was prepared in the same manner as in Example 2, except that treated silica 2 prepared in Preparation Example 2 was used instead of treated silica 1, and a silicone rubber composition (7) was prepared in the same manner as in Example 1. Using the obtained composition, a test sheet (7) was produced in the same manner as in Example 1, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 4.

[0075] [Comparative Example 1] A base compound (7) was prepared in the same manner as in Example 1, except that polymer 6 synthesized in Synthesis Example 6 was used instead of polymer 1, and a silicone rubber composition (8) was prepared in the same manner as in Example 1. A test sheet (8) was prepared using the obtained composition in the same manner as in Example 1, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 5.

[0076] [Comparative Example 2] A base compound (8) was prepared in the same manner as in Example 1, except that polymer 7 synthesized in Synthesis Example 7 was used instead of polymer 1, and a silicone rubber composition (9) was prepared in the same manner as in Example 1. Using the obtained composition, a test sheet (9) was produced in the same manner as in Example 1, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 5.

[0077] [Comparative Example 3] A base compound (9) was prepared in the same manner as in Example 1, except that polymer 8 synthesized in Synthesis Example 8 was used instead of polymer 1, and a silicone rubber composition (10) was prepared in the same manner as in Example 1. Using the obtained composition, a test sheet (10) was produced in the same manner as in Example 1, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 5.

[0078] [Comparative Example 4] A base compound (10) was prepared in the same manner as in Example 2, except that treated silica 3 prepared in Comparative Preparation Example 1 was used instead of treated silica 1, and a silicone rubber composition (11) was prepared in the same manner as in Example 2. Using the obtained composition, a test sheet (11) was produced in the same manner as in Example 2, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 5.

[0079] [Comparative Example 5] A base compound (11) was prepared in the same manner as in Example 2, except that treated silica 4 prepared in Comparative Preparation Example 2 was used instead of treated silica 1, and a silicone rubber composition (12) was prepared in the same manner as in Example 2. Using the obtained composition, a test sheet (12) was produced in the same manner as in Example 2, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 5.

[0080] [Comparative Example 6] A base compound (12) was prepared in the same manner as in Example 6, except that polymer 6 synthesized in Synthesis Example 6 was used instead of polymer 1, and a silicone rubber composition (13) was prepared in the same manner as in Example 6. A test sheet (13) was prepared using the obtained composition in the same manner as in Example 6, and the hardness, tensile strength, elongation at break, and compression set were measured in the same manner as above. The measurement results are shown in Table 5.

[0081] [Table 1]

[0082] [Table 2]

[0083] [Table 3]

[0084] [Table 4]

[0085] [Table 5]

[0086] The results shown in Tables 4 and 5 reveal the following: The millable silicone rubber compositions of Examples 1 to 5 and 7 of the present invention, which contain an addition reaction curing agent, have smaller compression set than Comparative Examples 1 to 3, which use organopolysiloxanes in which the amount of vinyl groups relative to the methyl groups bonded to the silicon atoms of the aminosilane is less than 0.03 mol % or more than 0.30 mol % on both ends. Moreover, it was found that Example 2 had a smaller compression set than Comparative Example 4, which used treated silica 3 without vinyltrimethoxysilane, and Comparative Example 5, which used treated silica 4 with a hydrophobicity of less than 40. It was found that Example 6, which contained an organic peroxide curing agent, had a smaller compression set than Comparative Example 6, which used an organopolysiloxane in which dimethylsiloxane with silanol ends and an aminosilane in which the amount of vinyl groups relative to the methyl groups bonded to the silicon atoms was less than 0.03 mol %. [Industrial Applicability]

[0087] The millable silicone rubber composition of the present invention can be suitably used for applications involving contact with food (e.g., food containers and packaging materials) when an addition reaction curing agent, which is a combination of an organohydrogenpolysiloxane and a hydrosilylation catalyst, is used as the curing agent (C), and can be suitably used for electric wire applications when an organic peroxide curing agent is used as the curing agent (C).

Claims

1. (A) a condensation product of the following (A-1) and (A-2): 100 parts by mass of an organopolysiloxane in which alkenyl groups bonded to silicon atoms in components (A-1) and (A-2) account for 0.03 to 0.30 mol %, relative to the number of substituents other than alkenyl groups bonded to silicon atoms in components (A-1) and (A-2), (A-1) An organopolysiloxane having silanol groups at both molecular chain terminals and represented by the following general formula (1), which contains less than 5,000 ppm of low-molecular-weight siloxanes with a degree of polymerization of 20 or less: 【Chemistry 1】 (In formula (1), R 1 may be the same or different and are monovalent hydrocarbon groups having 1 to 12 carbon atoms, and m is a number from 2 to 1,000. (A-2) A silane having two dialkylaminosilyl groups in one molecule, represented by the following general formula (2): 【Chemistry 2】 (In formula (2), R 2 may be the same or different and are monovalent hydrocarbon groups having 1 to 12 carbon atoms; R 3 may be the same or different and are alkyl groups having 1 to 4 carbon atoms. (B) 5 to 100 parts by mass of a treated silica having a hydrophobicity degree of 40 or more and treated with a mixture of a vinyl group-containing alkoxysilane and / or a vinyl group-containing organosilazane in an amount such that the vinyl group is 0.0001 mole or more per 100 parts by mass of silica, and 10 parts by mass of a dimethylpolysiloxane having silanol groups at both ends, an average degree of polymerization of 4, and a viscosity at 25° C. of 15 mPa s, and (C) Effective amount of hardener A millable type silicone rubber composition comprising:

2. 2. The millable silicone rubber composition according to claim 1, wherein component (C) is an addition reaction curing agent which is a combination of an organohydrogenpolysiloxane and a hydrosilylation catalyst.

3. 2. The millable silicone rubber composition according to claim 1, wherein component (C) is an organic peroxide curing agent.

4. A cured product of the millable type silicone rubber composition according to any one of claims 1 to 3.

5. 5. The cured product according to claim 4, wherein the total content of low molecular weight siloxane components having a degree of polymerization of 20 or less contained in the cured product is less than 5,000 ppm.

Citation Information

Patent Citations

  • Manufacture of organosilicon condensation product

    JP1990235931A

  • Silicone rubber composition

    JP1994136270A

  • Silicone rubber composition

    JP1994322273A

  • Production of organopolysiloxane with high degree of polymerization

    JP1995026020A

  • Production of silicone rubber

    JP1995070441A